(untitled) (Konturen, 2010)
Freud begins his well-known essay on the Uncanny with a disclaimer that raises the question of why he writes the essay in the first place. This text argues that the explanation is to be found in the shift his thinking was undergoing at the time, not only in moving "Beyond the Pleasure Priniple" but also in rethinking its relation to Anxiety.